2009
DOI: 10.1074/jbc.m109.013565
|View full text |Cite
|
Sign up to set email alerts
|

D-loop of Actin Differently Regulates the Motor Function of Myosins II and V

Abstract: To gain more information on the manner of actin-myosin interaction, we examined how the motile properties of myosins II and V are affected by the modifications of the DNase I binding loop (D-loop) of actin, performed in two different ways, namely, the proteolytic digestion with subtilisin and the M47A point mutation. In an in vitro motility assay, both modifications significantly decreased the gliding velocity on myosin II-heavy meromyosin due to a weaker generated force but increased it on myosin V. On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…One is that because the rate-limiting step in the myosin V ATPase cycle is ADP release (40), the slower transition from weak to strong binding may not be deleterious for this myosin. Consistent with this possibility, Kubota et al (41) reported that the M47A/E360H mutation of Dictyostelium actin slows down the transition of the leading head from the weak to the strong binding state, but it does not reduce gliding velocity. The second possibility is that the conformational states of the actin subunits required for myosin V motility differ from those required for myosin II motility.…”
Section: Discussionsupporting
confidence: 56%
“…One is that because the rate-limiting step in the myosin V ATPase cycle is ADP release (40), the slower transition from weak to strong binding may not be deleterious for this myosin. Consistent with this possibility, Kubota et al (41) reported that the M47A/E360H mutation of Dictyostelium actin slows down the transition of the leading head from the weak to the strong binding state, but it does not reduce gliding velocity. The second possibility is that the conformational states of the actin subunits required for myosin V motility differ from those required for myosin II motility.…”
Section: Discussionsupporting
confidence: 56%
“…It is noteworthy that Rng2CHD did not inhibit actin filament movement on myosin V HMM, which is well established to move actin filaments processively with a lever arm swing (Forkey et al, 2003, Kodera et al, 2010. In line with this finding, two actin mutations, M47A (Kubota et al, 2009) and G146V (Noguchi et al, 2012), both of which likely perturb conformational changes of actin filaments, inhibit actin movements on myosin II, but not on myosin V. We suggest that the movement by myosin II, which is a fast and non-processive motor, requires some unidentified structural property of actin filaments which is dispensable for the slow and processive myosin V involving the lever arm swing. Further studies are needed to understand the mechanism by which actin filaments structurally altered by Rng2CHD fails to move on myosin II.…”
Section: The Mechanism By Which Structural Changes Of Actin Filamentssupporting
confidence: 66%
“…In fact, tyrosine phosphorylation of actin can protect its D-loop structure from protease cleavage, resultant in a more stable conformation of the actin D-loop than the unphosphorylated form (Baek et al, 2008). Conformational stability of the D-loop holds much importance in conferring cell motile properties, which if unstable can result in a weakened contractile force and much reduced gliding velocity (Kubota et al, 2009). Our finding of reduced ACTB tyrosine phosphorylation in the PFTK1-suppressed cells would seem to be in line with the development of a less stable actin structure, which could have contributed to the repression on HCC cell migration.…”
Section: Discussionmentioning
confidence: 99%